Analisis Karakteristik, Perilaku, dan Motivasi Perjalanan Wisatawan Asal Sulawesi Utara ke Jakarta - Ade Suherlan (Faculty of Economic and Business, 2014)
This study aims to analyze the characteristics, behaviors and motivations of tourists from North Sulawesi trip to Jakarta. The research methodology used is descriptive qualitative method. The data used is primary data and secondary data collection method through survey questionnaires, interviews, and focus group discussion. Data analysis used SPSS statistical analysis includes frequency and cross-tab analysis, and SWOT analysis. The results of this study of which are domestic tourists from North Sulawesi classified as